A new species of the genus Madecorphnus (Coleoptera: Scarabaeidae: Orphninae) from Madagascar - Frolov, Andrey V.; Smith, Andrew B.t.; Akhmetova, Lilia A. (Zootaxa, 2017)
Madagascar has a unique and diverse Orphninae (Coleoptera: Scarabaeidae) fauna with four genera and 39 described species (Paulian 1977, Frolov et al. 2016). Half of these species belong to the genus Madecorphnus Paulian, 1992 (Paulian 1992, Frolov 2010a,b, 2012, 2014). The purpose of this paper is to describe a new species of Madecorphnus and provide a new record for M. dentatus Frolov, 2010.